Innovative Alveolar Ridge Preservation Surgical Technique with Immediate Dental Implant Placement: A Retrospective Case Report of 1-Year Follow-Up - Grassi, Andrea; Monica, Daniele; Minetti, Elio; Ballini, Andrea; Gianfreda, Francesco; Bollero, Patrizio; Cicciù, Marco; Mastrangelo, Filiberto (European Journal of Dentistry, 2023)
Following tooth extraction, the alveolar ridge undergoes morphological and dimensional changes, including a clot formation that is gradually replaced by granulation tissue. Studies indicate that both horizontal and vertical ridge dimensions decrease after extraction; however, these changes can be mitigated through grafting with biomaterials and barrier membranes. Alveolar ridge preservation (ARP) techniques are employed to counteract bone resorption postextraction, encompassing periosteal inhibition and modified periosteal inhibition (MPI) techniques. The Degidi clot chamber technique offers a means to achieve biomaterial-free extraction sockets, promoting healing and osteointegration. This study aims to present the first rehabilitation of a postextraction dental implant in the maxilla using an innovative ARP procedure via a MPI technique. The technique does not involve autologous or heterologous grafting materials; instead, a cortical lamina and a customized screw are used in conjunction with the blood clot. The primary objective is to protect the vestibular cortical bone from preosteoclastic aggression, which can trigger bone resorption. The technique employs a 0.5-mm cortical lamina to mechanically shield the vestibular cortical bone, preventing vestibular cortical bone resorption and increasing its thickness without the need for biomaterial insertion, relying on the blood clot. The effectiveness of the technique was assessed through a 12-month postimplantation cone-beam computed tomography scan, revealing a 0.5-mm increase. Although based on a single case, the 1-year follow-up results are promising, and further studies are warranted to validate the technique's efficacy.
Keywords: alveolar ridge preservation; periosteal inhibition; modified periosteal inhibition; cortical lamina; dental implant; implant survival